English teachers’ perceptions of supplemental teaching during the pandemic - Corpin, Cesar L. (Journal of Language and Pragmatics Studies, 2024)
The coronavirus disease, often known as COVID-19, has been a global pandemic since March 2020. According to UNESCO, schools in approximately 100 nations, including the Philippines, are shuttered due to a public health emergency. Due to the condition, teachers migrated from face-to-face instruction to modular learning, online learning, blended learning, and other learning modes. Teachers in Tacloban City switched to modular modality and other forms of learning to reach out to our students. Supplemental teaching was designed as one type of teaching approach in the classroom. Teachers' perceptions of supplemental teaching in English language acquisition were analyzed in this study. Their perspectives were examined in three areas: their opinions on using online platforms, their attitudes toward language teaching and preparations, and their perceptions of the usefulness of online supplemental teaching. The study utilized a qualitative design that gathered in-depth information through a semi-structured interview. The responses of 12 junior and senior high school English instructors at Sagkahan National High School were elicited through an interview. During the COVID-19 pandemic, 7 out of 12 participants had a favorable opinion of the effectiveness of supplemental teaching-learning methods, according to the findings of this study. However, 5 of the 12 respondents disagreed about its usefulness. Even though teachers confront numerous challenges in the online teaching process, they can demonstrate the proper attitude toward using technology to educate online amidst the pandemic.